Profil Kecerdasan Adversitas (Adversity Quotient) Siswa Kelas XII SMAN 1 Tarakan - Utami, Sri; Azizah, Nur; Hajaroh, Mami; Eliasa, Eva Imania; Sovayunanto, Riski; Siswoko, Heri (Quanta : Jurnal Kajian Bimbingan dan Konseling dalam Pendidikan, 2024)
This study aims to determine the description of Adversity of class XII students of SMAN 1 Tarakan. In class XII students who have a series of tasks that must be fulfilled as a graduation requirement.  Although the government in the Circular Letter (SE) of the Minister of Education and Culture Number 1 of 2021 has eliminated the national exam, it requires resilience in completing tasks as a graduation requirement, one of which is taking the School Examination and has completed the entire learning program. besides that, class XII students are also preoccupied with the choice of continuing studies after graduating from high school. This study uses a quantitative approach that is descriptive in nature with a survey method. The population in this study were students of class XII SMAN 1 Tarakan with a total of 362 students. Sampling in this study used simple random sampling, by first calculating the number of samples using the Slovin formula, so that the number of research samples obtained was 190 students. Data collection using Adversity Response Profile (ARP). Instrument testing with expert validation (expert judgment), namely experts in the field of counseling and language experts. The reliability test results show that the reliability index of the adversity quotient instrument is 0.920. The index shows that the instrument has a very high level of reliability and can be used in research. Research results 39 people (21%) were in the high category or climbers, 151 people (79%) were in the medium category or campers, and the low category or quitters 0%.